2017
DOI: 10.7860/jcdr/2017/26656.10563
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Antiplaque Efficacy of Coconut Oil Pulling and a Placebo, Among Dental College Students: A Randomized Controlled Trial

Abstract: Oil pulling is effective in controlling plaque levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(36 citation statements)
references
References 11 publications
0
36
0
Order By: Relevance
“…The results showed significant decrease in the mean plaque scores and they concluded that oil pulling is effective in controlling plaque levels. 42 Earlier in 2016, Peedikayil conducted a study on a total of fifty female children aged between 8-12 years for the evaluation of the antibacterial efficacy of coconut oil in comparison with chlorhexidine mouthwash. The treatment regimen (swishing) continued for 30 days with coconut oil or with chlorhexidine.…”
Section: Studies Related To Effects Of Coconut Oil Pulling On Oral Hementioning
confidence: 99%
“…The results showed significant decrease in the mean plaque scores and they concluded that oil pulling is effective in controlling plaque levels. 42 Earlier in 2016, Peedikayil conducted a study on a total of fifty female children aged between 8-12 years for the evaluation of the antibacterial efficacy of coconut oil in comparison with chlorhexidine mouthwash. The treatment regimen (swishing) continued for 30 days with coconut oil or with chlorhexidine.…”
Section: Studies Related To Effects Of Coconut Oil Pulling On Oral Hementioning
confidence: 99%
“…A total of four randomised-controlled studies were included in this systematic review [ 8 , 9 , 10 , 11 ] (Tables 3 and 4 ). All the published data described patients treated between 2015 and 2019.…”
Section: Resultsmentioning
confidence: 99%
“…In three studies, this was compared to water as a control, and the other study used chlorhexidine. Only one study detailed clearly the complete oral hygiene adjustment during the study period and documented the advice given to participants to stop brushing for the study duration [9]. It was unclear what other oral hygiene habits were enforced in the other three studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations